Abdominal aortitis on PET CT: A case report and review of the literature. (2015) - Foley, J.; Mullan, D.; Mohan, H.; Schmidt, K.
Highlights: Abdominal aortitis occurs in patient with systemic vasculitis. It should be considered in patients who present with unexplained abdominal pain and weight loss on a background of a vasculitic condition. Aortitis is the inflammation of the aortic wall and occurs most commonly due to an infective or autoimmune process. CT, MRI and PET scans all have functional diagnostic roles in aortitis. The gold standard of treatment for aortitis is glucocorticoids. Abstract: Introduction: Aortitis often occurs in patients with systemic vasculitis. Presentation of case: We reported a 73 year old man with giant cell arteritis who was presented with abdominal pain and weight loss. Discussion: Aortitis was diagnosed on PET-CT scan performed because initial investigations raised the possibility of pancreatic pathology. Conclusion: This case highlights the utility of PET-CT in the diagnosis of abdominal aortitis and the need to consider aortitis as a differential in patients with abdominal pain with a history of vasculitis.